The Perceived Benefits of Upskilling Medical Technologists in the Bataan Province in regard to Specimen Collection, Handling, and Processing During the COVID-19 Pandemic - Sy, Julianna Gabrielle; Marquez, Izabella Anne; Santos, Alexandria Mae; Sy, Katherine Anne; Yu, Monica Maegan (International Journal of Arts, Sciences and Education, 2021)
The COVID-19 pandemic has greatly impacted the lives of many people in the Philippines, specifically those who work in healthcare. With the sudden rise of COVID-19 cases, many of those working in the medical field had to upskill and undergo training programs to adapt to the new normal, including medical technologists. This study aims to understand whether the training programs were beneficial to the medical technologists in improving their skills in specimen collection, handling, and processing for the pandemic, based on their perceptions. It also seeks to identify the laboratory services most and least affected by the pandemic, as well as the training program deemed most useful. A cross-sectional descriptive research design was employed for this study, and the data collection was done through online Google Forms surveys. Respondents consisted of 132 medical technologists from Bataan Province who have undergone training programs for the COVID-19 pandemic. From their responses, it was discovered that medical technologists found the training programs to be highly beneficial for most skills, and only helpful for some skills. The majority of the respondents underwent online training programs, and this was deemed the most useful. For laboratory services, the least affected service was urinalysis, and the most affected service was microbiology. In the future, further studies should be conducted in wider sample sizes to thoroughly assess the benefits of training programs on medical technologists.